Human Platelet Antigen Alleles in 998 Taiwanese Blood Donors Determined by Sequence-Specific Primer Polymerase Chain Reaction. (20th June 2013) - Pai, Shun-Chung; Burnouf, Thierry; Chen, Jen-Wei; Lin, Liang-In
Abstract : Polymorphism of human platelet antigens (HPAs) leads to alloimmunizations and immune-mediated platelet disorders including fetal-neonatal alloimmune thrombocytopenia (FNAIT), posttransfusion purpura (PTP), and platelet transfusion refractoriness (PTR). HPA typing and knowledge of antigen frequency in a population are important in particular for the provision of HPA-matched blood components for patients with PTR. We have performed allele genotyping for HPA-1 through -6 and -15 among 998 platelet donors from 6 blood centers in Taiwan using sequence-specific primer polymerase chain reaction. The HPA allele frequency was 99.55, and 0.45% for HPA-1a and -1b; 96.49, and 3.51% for HPA-2a and -2b; 55.81, and 44.19% for HPA-3a and -3b; 99.75, and 0.25% for HPA-4a and -4b; 98.50, and 1.50% for HPA-5a and -5b; 97.75 and 2.25% for HPA-6a and -6b; 53.71 and 46.29% for HPA-15a and -15b. HPA-15b and HPA-3a, may be considered the most important, followed by HPA-2, -6, -1, -5, and -4 systems, as a cause of FNAIT, PTP, and PTR based on allele frequency. HPA-4b and HPA-5b role cannot be excluded based on their immunogenicity. A larger-scale study will now be conducted to confirm these hypotheses and to establish an apheresis donor database for the procurement of HPA-matched apheresis platelets for patients with PTR.